ZnF2‐modified AlF3‐based fluoride glasses with enhanced mid‐infrared 3.5 μm emission. Issue 7 (25th March 2022) - Zhang, Jie; Wang, Ruicong; Liu, Mo; Wang, Shunbin; Zhang, Zhi; Farrell, Gerald; Jia, Shijie; Wang, Pengfei
Abstract: A novel ZnF2 –AlF3 based fluoride glass was prepared. The introduction of ZnF2 can lower the phonon energy of AlF3 –BaF2 –YF3 –SrF2 glass while maintaining good thermal stabilities. The mid‐infrared emission properties of Er 3+ ‐doped ZnF2 –AlF3 –YF3 –SrF2 –BaF2 (ZAYSB) glasses were investigated. Enhanced 3.5 μm and 2.7 μm emissions were observed with an incremental increase in the content of ZnF2 . In addition, the Er 3+ ‐doped ZAYSB glass was shown to have a large emission cross‐section of 3.5 μm. This study indicates that this ZAYSB glass is a promising glass material for 3.5 μm fiber‐laser applications.